Pengaruh Harga, Variasi Produk Dan Kualitas Produk Terhadap Keputusan Pembelian Keripik Singkong Saat Pandemi COVID-19 Di UKM Cap Rumah Adat Minang Medan - Fadhila, Fadhila; Munte, Sirmas; Polewangi, Yudi Daeng (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2022)
Buying decisions are part of consumer behavior; consumer behavior is research on how people, groups, and organizations select, buy, use, and how goods, services, ideas, or experiences satisfy their needs and wants. The purpose of this study was to determine the effect of price, product variation, and product quality on purchasing decisions during the COVID-19 pandemic at UKM (Small Medium Enterprise) Cap Rumah Adat Minang Medan. The type of research is associative research. The populations in this study were all customers who bought cassava chips during the COVID-19 pandemic at UKM Cap Rumah Adat Minang Medan. The samples in the study were 100 consumers. The sampling technique used was non-robability sampling with an accidental sampling approach. Then, data collections methods used were questionnaires, interviews, and a literature study. The analytical method used was the multiple linear regression analysis methods which were processed with SPSS 25.0 software. The results obtained were that price, product variation, and product quality simultaneously affect the decision to buy cassava chips during the COVID-19 pandemic at UKM Cap Rumah Adat Minang Medan at age 20 with a score of 40.583 and 0.000 and age 21-25 with a score of 75.332 and 0.000. Meanwhile, price, product variation, and product quality simultaneously did not affect the decision to buy cassava chips during the COVID-19 pandemic at UKM Cap Rumah Adat Minang Medan at the age of 26-30 with a score of 0.249 and 0.000, age 30 with a score of 1.109 and 0.361, and the highest coefficient of determination was at the age of 21-25 with a score of 90.7%. Thus, price, product variety, and product quality had a very strong influence on buying decisions, the remaining 9.3% was influenced by other factors outside of this research variable.